Definiteness - Lyons, Christopher (Cambridge Textbooks in Linguistics, 1999)
This 1999 textbook investigates definiteness both from a comparative and a theoretical point of view, showing how languages express definiteness and what definiteness is. It surveys a large number of languages to discover the range of variation in relation to definiteness and related grammatical phenomena, such as demonstratives, possessives and personal pronouns. It outlines work done on the nature of definiteness in semantics, pragmatics and syntax, and develops an account on which definiteness is a grammatical category represented in syntax as a functional head (the widely discussed D). Consideration is also given to the origins and evolution of definite articles in the light of the comparative and theoretical findings. Among the claims advanced are that definiteness does not occur in all languages, though the pragmatic concept which it grammaticalizes probably does.